Analysis of Tear Cytokines and Clinical Correlations in Sjögren Syndrome Dry Eye Patients and Non–Sjögren Syndrome Dry Eye Patients - Lee, Sang Yeop; Han, Soo Jung; Nam, Sang Min; Yoon, Sang Chul; Ahn, Ji Min; Kim, Tae-Im; Kim, Eung Kweon; Seo, Kyoung Yul (American journal of ophthalmology, 2013)
To compare concentrations of tear cytokines in 3 groups composed of Sjögren syndrome (SS) dry eye, non–Sjögren syndrome (non-SS) dry eye, and normal subjects. Correlations between ocular surface parameters and tear cytokines were also investigated. Prospective cross-sectional study. SS dry eye patients (n = 24; 40 eyes) were diagnosed with primary SS according to the criteria set by the American-European Consensus Group. Non-SS dry eye patients (n = 25; 40 eyes) and normal subjects (n = 21; 35 eyes) were also enrolled. Tear concentrations of interleukin (IL)-17, IL-6, IL-10, IL-4, IL-2, interferon γ (IFN-γ), and tumor necrosis factor α (TNF-α) were measured by a multiplex immunobead assay. Ocular Surface Disease Index (OSDI), tear film breakup time (TBUT), Schirmer I test, and fluorescein staining scores were obtained from dry eye patients. All cytokine levels except for IL-2 were highest in the SS group, followed by non-SS dry eye group and control subjects. Concentrations of IL-17, TNF-α, and IL-6 were significantly different among the 3 groups (IL-17: SS > control P < .001, non-SS > control P = .042, SS > non-SS P < .001; TNF-α: SS > control P = .006, non-SS > control P = .034, SS > non-SS P = .029; IL-6: SS > control P = .002, non-SS > control P = .032, SS > non-SS P = .002). IL-17 was significantly correlated with TBUT (R = −0.22, P = .012) and Schirmer I test (R = −0.36, P = .027) scores in the SS group. IL-6 was significantly correlated only with TBUT (R = −0.38, P = .02) in the non-SS group. Differences in tear cytokine levels and correlation patterns between SS dry eye and non-SS dry eye patients suggest the involvement of different inflammatory processes as causes of dry eye syndrome.